2020
DOI: 10.1158/1535-7163.mct-19-0270
|View full text |Cite
|
Sign up to set email alerts
|

Modulating TAK1 Expression Inhibits YAP and TAZ Oncogenic Functions in Pancreatic Cancer

Abstract: YAP and TAZ are central determinants of malignancy; however, their functions remain still undruggable. We identified TGFb-activated kinase 1 (TAK1) as a central hub integrating the most relevant signals sustaining pancreatic cancer aggressiveness and chemoresistance. Glycogen synthase kinase (GSK)3 is known to stabilize TAK1, and its inhibition causes a reduction in TAK1 levels. Here, we hypothesized that TAK1 could sustain YAP/TAZ program, and thus, modulation of TAK1 expression through the inhibition of GSK3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 41 publications
(38 reference statements)
2
35
0
Order By: Relevance
“…2). It has been shown that LY2090314 treatment in conjunction with nab-paclitaxel in a preclinical model of pancreatic cancer prolonged mice survival (82). However, regimens consisting of LY2090314 in combination with pemetrexed and carboplatin, demonstrated suboptimal safety profiles and minimal clinical efficacy in patients with advanced pancreatic cancer in a previous phase I clinical trial (83).…”
Section: Signaling Pathways Involved In Csc Stemness and Potential Tamentioning
confidence: 99%
“…2). It has been shown that LY2090314 treatment in conjunction with nab-paclitaxel in a preclinical model of pancreatic cancer prolonged mice survival (82). However, regimens consisting of LY2090314 in combination with pemetrexed and carboplatin, demonstrated suboptimal safety profiles and minimal clinical efficacy in patients with advanced pancreatic cancer in a previous phase I clinical trial (83).…”
Section: Signaling Pathways Involved In Csc Stemness and Potential Tamentioning
confidence: 99%
“…GSE137265) were examined by using Illumina Human 48k gene chips (D-103-0204; Illumina) as previously described in ref. 9.…”
Section: Gene Expression and Pathway Analysesmentioning
confidence: 99%
“…We recently identified the serine/threonine kinase TGFb-activated kinase 1 (TAK1) as a central hub integrating the most relevant signals from various cytokines (5,6) and sustaining, in turn, resistance to chemotherapeutic treatments through the activation of different transcription factors, including AP-1, NF-kB (7,8), and YAP/TAZ (9). In particular, we demonstrated that targeting the kinase activity of TAK1 dramatically led to a proapoptotic phenotype and, in turn, to a significantly higher sensitivity to chemotherapy and radiotherapy in pancreatic (10) and esophageal carcinoma (11).…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that TAK1 mediated YAP phosphorylation, resulting in a reciprocal antagonism between Hippo-YAP/TAZ and NF-κB signalling during osteoarthritis pathogenesis (Deng et al, 2018). The other study showed that TAK1 regulated YAP-derived oncogenicity in pancreatic cancer (Santoro et al, 2020). Further studies are warranted to characterize the exact regulated mechanism of YAP and NF-κB in the regulation of in ammatory cell functions in nasal polyps to nd out if there was a bi-directional control mechanism.…”
Section: Discussionmentioning
confidence: 99%